Large Rhinolith Mimicking Atypical Odontogenic Pain: Case Report and Brief Review of the Literature - Zahra Vasegh; Mitra Ghazizadeh Ahsaie (Case Reports in Dentistry)
Rhinoliths are rare calcified entities in the nasal fossa, frequently originating around a nidus near the midway point in the inferior meatus, where the passage is the narrowest. They can be clinically asymptomatic and undetected for years. In this study, we present a rare case of large rhinolith mimicking atypical odontogenic pain in a 40-year-old Caucasian female in the left nasal cavity. The lesion was detected in the CBCT and removed uneventfully.